2002
DOI: 10.1002/1099-0682(20022)2002:2<465::aid-ejic465>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

New Helical Complexes with a Bis(bidentate) Schiff Base Ligand Containing a Flexible Spacer

Abstract: Neutral complexes with the general empirical formula M(PTs) [M: Mn, Fe, Co, Cu, Zn, and Cd; H2PTs: N,N′‐bis(2‐tosylaminobenzylidene)‐1,3‐diaminopropane] were obtained by means of an electrochemical procedure. All complexes were characterised by elemental analyses, mass spectrometry, IR and 1H NMR spectroscopy, and magnetic measurements, where appropriate. Recrystallisation of the cobalt, copper, and zinc complexes yielded single crystals of [Co(PTs)] (1), [Cu(PTs)]·1.5CH3CN (2) and [Zn(PTs)]2·1.5H2O·CH3CN (3).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Two oxygen atoms from the tosyl groups interact weakly with each metal centre (Zn–O distance = 2.69 Å). All the other bond lengths are similar to those found in other tetrahedral zinc( II ) complexes with similar N 4 Schiff bases 15,19,24…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Two oxygen atoms from the tosyl groups interact weakly with each metal centre (Zn–O distance = 2.69 Å). All the other bond lengths are similar to those found in other tetrahedral zinc( II ) complexes with similar N 4 Schiff bases 15,19,24…”
Section: Resultssupporting
confidence: 82%
“…Two oxygen atoms from the tosyl groups interact weakly with each metal centre (Zn–O distances range from 2.65 to 2.87 Å). All other bond lengths are similar to those found in other tetrahedral zinc( II ) complexes with related Schiff‐base ligands 15,19,24. The phenyl rings of the diarylmethane spacer are face‐to‐face π‐stacked with those on the adjacent ligand strand [centroid–centroid distances: rings C22 to C27 and C63 to C68 = 4.19 Å; rings C15 to C20 and C55 to C60 = 4.01 Å; angles between ring planes: rings C22 to C27 and C63 to C68 = 27.11(2)°, rings C15 to C20 and C55 to C60 = 18.02(2)°].…”
Section: Resultssupporting
confidence: 73%
“…[9] The 13 C NMR spectra of complexes 6-9 in CDCl 3 consist of the expected signals. In all cases, the disappearance of the NH protons from the free ligands was observed, which is in agreement with the double deprotonation of the Schiff bases.…”
mentioning
confidence: 93%
“…

The metal complexes of ligands I, a pyrrol-2-yl Schiff base or pyrrol-2ylmethyleneamine, have been known for a long time. Linear-spacer-bridged bis(pyrrol-2ylmethyleneamine)s and their complexes with metal ions were recently reported, [5][6][7][8][9] which showed that both the preparation of the ligands and the complexes were highly efficient, and the metal complexes formed by pyrrol-2-ylmethyleneamines possessed good solubility in common solvents. Linear-spacer-bridged bis(pyrrol-2ylmethyleneamine)s and their complexes with metal ions were recently reported, [5][6][7][8][9] which showed that both the preparation of the ligands and the complexes were highly efficient, and the metal complexes formed by pyrrol-2-ylmethyleneamines possessed good solubility in common solvents.

…”
mentioning
confidence: 99%
See 1 more Smart Citation